Molecular phylogeny and taxonomy of Fibroporia (Basidiomycota) in China - Chen, Yuan-Yuan; Li, Hai-Jiao; Cui, Bao-Kai (Phytotaxa, 2015)
Taxonomic and phylogenetic studies on the Chinese species of Fibroporia were carried out. Fibroporia albicans sp. nov. is described and illustrated on the basis of collections originating from Jiangxi and Xizang provinces, based on morphology and phylogenetic analysis of ITS rDNA sequences. Morphologically, it is characterized by resupinate, annual basidiocarps, white to cream-colored pore surface when fresh, becoming cream to cream-buff upon drying, small pores (6–8 per mm), presence of white to cream rhizomorphs, a dimitic hyphal system with clamped generative hyphae, fusoid cystidioles, and oblong to ellipsoid basidiospores; moreover, it causes a brown rot. Molecular data suggested a close relationship between Fibroporia albicans and F. citrina. Six species of Fibroporia form a monophyletic entity with 100% MP and 1.00 BPP supports. An identification key to the Chinese species of Fibroporia is provided.